Impact of co‐morbidities on resource use and adherence to guidelines among commercially insured adults with new visits for back pain. Issue 6 (16th May 2017) - Rundell, Sean D.; Gold, Laura S.; Hansen, Ryan N.; Bresnahan, Brian W.
Abstract: Rationale, aims and objectives: To assess if co‐morbidity is associated with higher use of back‐related care and adherence to back pain guidelines. Methods: We conducted a retrospective cohort study using administrative claims data from 2007‐2011. We included individuals ≥18 years with an index visit for back pain. Co‐morbidities were measured 12 months prior to index. Co‐morbidity burden was measured using Quan's Co‐morbidity Index. Co‐morbidities categories were measured using chronic condition indicators from the Agency for Healthcare Research and Quality. Total lumbar spine‐related resource use for three years was ascertained using procedure codes. A clustering algorithm identified higher long‐term utilizer. We identified initial use from day 0‐42 for several categories of spine‐related care. We used logistic regression to test the association between co‐morbidities and resource use. Results: Greater co‐morbidity burden was associated with higher long‐term spine‐related resource use. Those with ≥2 on Quan's Co‐morbidity Index had 29% higher odds of being a high back‐specific resource user compared to those with no co‐morbidities [Odds Ratio (OR): 1.29, 95% Confidence Interval (CI): 1.23‐1.35]. Greater co‐morbidity burden was associated with more frequent initial use of imaging, emergency visits, injections, and opioid fills; and less frequent initial use of medical and physical therapy visits. Co‐morbid musculoskeletal conditions had the strongest association with being a high utilizer of long‐term back‐specific resources (OR: 1.53, 95% CI: 1.50‐1.57). Conclusions: Co‐morbidity burden and the presence of specific chronic conditions, such as musculoskeletal conditions, were associated with high long‐term use of back‐related care and care inconsistent with guidelines.